Landscape in the Longue Duree - Tilley, Christopher (UCL Press, 2017)
Pebbles are usually found only on the beach, in the liminal space between land and sea. But what happens when pebbles extend inland and create a ridge brushing against the sky? Landscape in the Longue Durée is a 4,000 year history of pebbles. It is based on the results of a four-year archaeological research project of the east Devon Pebblebed heathlands, a fascinating and geologically unique landscape in the UK whose bedrock is composed entirely of water-rounded pebbles. Christopher Tilley uses this landscape to argue that pebbles are like no other kind of stone - they occupy an especial place both in the prehistoric past and in our contemporary culture. It is for this reason that we must re-think continuity and change in a radically new way by considering embodied relations between people and things over the long term. Dividing the book into two parts, Tilley first explores the prehistoric landscape from the Mesolithic to the end of the Iron Age, and follows with an analysis of the same landscape from the eighteenth into the twenty-first century. The major findings of the four-year study are revealed through this chronological journey: from archaeological discoveries, such as the excavation of three early Bronze Age cairns, to the documentation of all 829 surviving pebble structures, and beyond, to the impact of the landscape on local economies and its importance today as a military training camp. The results of the study will inform many disciplines including archaeology, cultural and art history, anthropology, conservation, and landscape studies.